Design and development of mathematics student worksheets based on problem based learning to improve understanding of spatial geometry in elementary schools - Sianturi, Roy; Siagian, Sahat; Sugiharto, Sugiharto (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This study aims to develop teaching materials in the form of Student Worksheets (LKPD) based on Problem-Based Learning for spatial geometry material in fifth grade elementary schools. The background of this study is the low mathematics learning outcomes and the limited teaching materials that can encourage active student involvement. The development process uses the ADDIE model with validation from material experts, media experts, and design experts which shows that the developed LKPD meets the criteria of very valid. The results of the effectiveness test show that this LKPD is able to improve conceptual understanding, active involvement, and student learning outcomes in mathematics learning. This study concludes that LKPD based on Problem-Based Learning is suitable for use as an alternative teaching material in elementary schools. The recommendation from this study is the need for teachers to integrate problem-based teaching materials into mathematics learning on an ongoing basis and to develop other materials and levels so that the results are broader and deeper.